International Law and World Order Problems - Njenga, F. X.; Ongoya, Elisha (The East African Law Journal, 2004)
We have received the news of the re vival of the East African Law Journal with a lot of excitement. This is a wel come development in the legal and academic circles in the East African region. This journal traces its life his- . tory back to the days of the defunct East African Community, which was established in 1967 and collapsed ten years later in 1977. It is recalled that the journal whose last publication was in 1977 was a joint publication of the Community and the Faculty of . Law, University of Nairobi. Like many other activities, which were conducted under the auspices of the Community, publication of the jour nal was also affected by the collapse of the Community and could not con tinue after its demise. Absence of such journals is untenable as it not only de nied scholars a forum for their schol arly works and dissemination of re search findings but also contributed to lowering the standards of legal practice and teaching in the region. It is in this context that the revival of the East African Law Journal is a welcome development, which will inter alia, al leviate those problems. The collapse of the East African Com munity was widely regretted in the region and the people of East Africa upon realising that it was a grave mis take to let the Community break have taken deliberate steps to revive it to- :: gether with its institutions deter- .1 mined that "it should never happen again." Revival of the East African Law Journal is a step towards that goal and . · ' indeed a clear testimony of determi nation of the East Africans towards solid regional integration. The importance of co-operation in different areas among the East Afri cans cannot be over emphasised. The · Treaty for the Establishment of the East African Community states · clearly in Article 5 that the" objectives of the Community shall be to develop policies and programmes aimed at q widening and deepening co-opera tion among the partner States in po litical, economic, social and cultural fields, research and technology, de- . fence, security, legal and judicial af fairs, for their mutual benefit." The Treaty also puts emphasis on the in- i· volvement of private sector/ civil so- L Undoubtedly the reintroduction of this journal plays a significant role in L ciety in the integration process. The J · work and contribution of the aca- ( I-. demic institutions in the integration ! process is of vital importance in or- T' der to avoid pit falls which lead to the collapse of the previous Community, which is a fact also, recognised by Treaty.
Keywords: Law and World Order Problems